Learning ClojureScript - Jarvis, W. David; Jarvis, W. David; Naccache, Rafik; Rohner, Allen (Packt Publishing, 2016)
Master the art of agile single page web application development with ClojureScriptAbout This BookSet up interactive development workflows for the browser or Node.js thanks to the ClojureScript ecosystemLearn the basics of interactive single page web app development taking advantage of the functional nature of ClojureScriptDelve into advanced rich web application development concepts such as Om, along with core.async, using zippers and logic programming, and preparing code for production with testing or optimizing via the Google Closure CompilerWho This Book Is ForThis book is for web application developers who want to benefit from the power of ClojureScript to get an agile and highly productive development platform that targets mainly browser JavaScript.You are not required to be fluent in Clojure, but it will be easier for you if you have a basic understanding of browser and server-side JavaScript.What You Will LearnUnderstand how the ClojureScript compiler operatesSet up interactive development workflows for ClojureScriptGrasp the basics of the ClojureScript language, including basic syntax, data structures, variable scoping, namespaces, and finally the powerful sequence abstractionDelve into advanced concepts such as functional programming, macro writing, asynchronous programming, app routing, and real-time webDevelop simple one page web applicationsExplore techniques to make your web apps aware of the external world through external or embedded database access or Oauth 2 integrationLearn more advanced ClojureScript concepts like in app routing, real-time webPrepare your work for production, getting insights into optional type-checking, writing portable Clojure/ClojureScript code, and testingIn DetailClojure is an expressive language that makes it possible to easily tackle complex software development challenges. Its bias toward interactive development has made it a powerful tool, enabling high developer productivity.In this book, you will first learn how to construct an interactive development experience for ClojureScript.. You will be guided through ClojureScript language concepts, looking at the basics first, then being introduced to advanced concepts such as functional programming or macro writing. After that, we elaborate on the subject of single page web applications, showcasing how to build a simple one, then covering different possible enhancements. We move on to study more advanced ClojureScript concepts, where you will be shown how to address some complex algorithmic cases. Finally, you'll learn about optional type-checking for your programs, how you can write portable code, test it, and put the advanced compilation mode of the Google Closure Compiler to good use.Style and approachThis book is a comprehensive reference guide on ClojureScript development for the front end, and will gradually help you master interactive ClojureScript development workflows, through detailed step-by-step information illustrated with annotated code samples.